Evaluation of KH560 on properties and environmental effects of electrolytic manganese slag-based cementitious materials - Ying Zhou; Yue Wang; Daikuan Huang; Yang Cao; Dabin Zhang (iScience)
Summary: KH560-modified electrolytic manganese slag (EMS)-based cementitious material (EP-K) was successfully prepared in this study through aqueous solution polymerization for use in deep grouting to repair leaking landfills. EP-K with 3 vol % KH560 exhibits higher compressive strength (125.14% higher) and lower permeability (61.29% lower) than before modification. The concentration of contaminants leached in deionized water meets safety standards. Fourier transform infrared (FTIR) and scanning electron microscope (SEM) analyses showed that the epoxy groups in KH560 reacted with the –OH groups of sodium polyacrylate to form a C–O–C structure, which enhanced the densification of the cementitious network. Also, the siloxy groups reacted with EMS to form a Si–O–Si linkage, which reduced holes and cracks. The integrated pollution indicator evaluation method was combined with the weight assignment technique to enhance evaluation efficiency and accuracy, advancing research on the performance and environmental impact of cementitious impermeable materials in solid waste landfills.